2014
DOI: 10.1007/s12032-014-0067-8
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of tobacco and DNA repair genes polymorphisms of XRCC1 and XRCC2 influence high risk of head and neck squamous cell carcinoma in northeast Indian population

Abstract: Tobacco consumption in various forms is one of the major risk factor for the development of head and neck squamous cell carcinoma. Polymorphisms in XRCC1 and XRCC2 genes may alter an individual's susceptibility to tobacco-related cancers. Here, we have investigated the interaction of XRCC1 (Arg399Gln) and XRCC2 (Arg188His) polymorphism and tobacco exposure in the progression of HNSCC in northeast Indian population. The population-based case-control study includes 110 HNSCC patients and 140 controls. The polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…We also found no association of XRCC1 c.839G>A and c.1196G>A SNPs with OPSCC risk, according to previous results from overall HNSCC studies (Sturgis et al 1999;Tae et al 2004;Demokan et al 2005;Matullo et al 2006;Li et al 2007;Harth et al 2008;Applebaum et al 2009;Csejtei et al 2009;Kowalski et al 2009;Gugatschka et al 2011;Al-Hadyan et al 2012;Yuan et al 2012). In contrast, the variant allele A of c.1196G>A SNP was associated with decreased risk (Olshan et al 2002;Kumar et al 2012;Khlifi et al 2014) and increased risk (Choudhury et al 2014) of overall HNSCC. The disparate results obtained in our study and previous studies may be, again, attributed to different HN tumor sites investigated in previous studies, since similar frequencies of the genotypes were seen in our control group and in the other controls.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…We also found no association of XRCC1 c.839G>A and c.1196G>A SNPs with OPSCC risk, according to previous results from overall HNSCC studies (Sturgis et al 1999;Tae et al 2004;Demokan et al 2005;Matullo et al 2006;Li et al 2007;Harth et al 2008;Applebaum et al 2009;Csejtei et al 2009;Kowalski et al 2009;Gugatschka et al 2011;Al-Hadyan et al 2012;Yuan et al 2012). In contrast, the variant allele A of c.1196G>A SNP was associated with decreased risk (Olshan et al 2002;Kumar et al 2012;Khlifi et al 2014) and increased risk (Choudhury et al 2014) of overall HNSCC. The disparate results obtained in our study and previous studies may be, again, attributed to different HN tumor sites investigated in previous studies, since similar frequencies of the genotypes were seen in our control group and in the other controls.…”
Section: Discussionsupporting
confidence: 79%
“…The roles of the OGG1 c.977C>G (Elahi et al 2002;Zhang et al 2004;Matullo et al 2006;Görgens et al 2007;Hall et al 2007;Kumar et al 2011;Mitra et al 2011), APEX1 c.444T>G (Matullo et al 2006;Li et al 2007); XRCC1 c.-77T>C, c.580C>T (Sturgis et al 1999;Olshan et al 2002;Tae et al 2004;Demokan et al 2005;Matullo et al 2006;Applebaum et al 2009;Csejtei et al 2009;Kowalski et al 2009;Gugatschka et al 2011;Kumar et al 2012), c.839G>A (Tae et al 2004;Applebaum et al 2009;Gugatschka et al 2011;Kumar et al 2012) and c.1196G>A (Sturgis et al 1999;Olshan et al 2002;Tae et al 2004;Demokan et al 2005;Matullo et al 2006;Li et al 2007;Harth et al 2008;Applebaum et al 2009;Csejtei et al 2009;Kowalski et al 2009;Gugatschka et al 2011;AlHadyan et al 2012;Kumar et al 2012;Yuan et al 2012;Choudhury et al 2014;Khlifi et al 2014) SNPs in overall HNSCC risk are still controversial or unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were reported in three other studies from North India on head and neck cancer, 45 hepatocellular carcinoma 46 and lung cancer. 47 Contrary to the results of the present study, some previous studies from North India have reported an increased risk with AA genotype of XRCC1p.Arg399Gln polymorphism in lung cancer, 48 head and neck cancer, 49 colorectal cancer 50 and prostate cancer. 51 Similarly, some studies from South India reported an association of increased risk with the AA genotype in gastric cancer, 52 colorectal cancer, 29 lung cancer, 53,54 cervical cancer, 55 Naso-pharyngeal cancer, 56 acute lymphoblastic leukemia 57 and acute myeloid leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies from the northeast India reported tobacco smoking as one of the strongest risk factor for HNC (Yadav et al, 2010;Talukdar et al, 2013;Choudhury and Ghosh, 2014;Ghosh et al, 2014a) . Moreover, it was seen that tobacco-betel quid chewing also had a very high impact on HNC risk (Sharan et al, 2012;Choudhury et al, 2014) . Tobacco in any form generates free radicals that deplete antioxidants and cause oxidative damage to DNA, proteins and lipids resulting in cancers.…”
Section: Discussionmentioning
confidence: 99%